Cambodia Economic Update, May 2020 : Cambodia in the Time of COVID-19 - World Bank Group (World Bank, Phnom Penh, 2020)
The global epidemiological and economic crisis unleashed by COVID-19 (Coronavirus) poses the greatest threat to Cambodia’s development in its 30 years of modern history. The three most affected sectors - tourism, manufacturing exports, and construction - contributed more than 70 percent of growth and 39.4 percent of total paid employment in 2019. Therefore, in the current year, Cambodia’s economy is likely to register its slowest growth since 1994, contracting between -1 percent (baseline) and -2.9 percent (downside). Poverty can increase between 3 and 11 percentage points from a 50 percent income loss that lasts for six months for households engaged in tourism, wholesale and retail trade, garment, construction, or manufacturing. The fiscal deficit can reach its highest level in 22 years, and public debt is expected rise to 35 percent of gross domestic product (GDP) by 2022. The authorities have introduced emergency measures to contain the outbreak and provide fiscal assistance to affected households, workers, and enterprises. To facilitate a robust recovery, the government will need to continue to ensure macroeconomic and financial sector stability and accelerate trade and investment reforms as well as encourage faster adoption of digital technologies.